Does rural financial development facilitate food production? Evidence from major wheat–producing provinces of China - Abbas Ali Chandio; Yasir A. Nasereldin; Irfan Khan; Yashuang Tang; Yuansheng Jiang (Cogent Food & Agriculture, 2023)
AbstractThe allocation of agricultural credit is an exceptional strategy for ensuring sustainable agricultural production. It increases farmers’ purchasing power and technical efficiency. In this study, we examine the long-run impact of agricultural credit on wheat production in nine major wheat—producing provinces of China from 1992–2020. The research also takes into account agrochemical inputs (such as fertilizer and pesticide), planting area, agricultural machinery, and rural labor force. Several advanced econometric techniques, such as cross—sectional dependence (CSD), Westerlund co—integration (second—generation approach), Feasible Generalized Least Squares (FGLS), Dynamic Ordinary Least Squares (DOLS), One—step Generalized Method of Moments (GMM), and panel causality tests, are utilized to conduct empirical estimation. The findings show that agricultural credit significantly increases wheat production. It has been proved that agricultural credit is an important factor in increasing grain production and ensuring food sustainability. Regarding agrochemical inputs, fertilizer use positively affects wheat production, whereas pesticide usage negatively affects wheat production. Other determinants influencing wheat production included planting area, agricultural machinery, and rural labor force. China’s agricultural credit and related policies have played a significant role in grain production since the country’s reform and opening up. China must consolidate poverty alleviation achievements and further develop the countryside under the current rural revitalization and food security strategies. Agricultural credit is essential in this process and should be expanded.